Pain and depression risk among elderly people living in a nursing home - ERGÜN, AYŞE (My University, 2009)
Giriş: Araştırma, bir huzurevinde kalan yaşlıların ağrı ve depresyon durumlarını, ağrı ile depresyon arasındaki ilişkiyi ve etkileyen faktörleri incelemek amacıyla planlanmıştır. Gereç ve Yöntem: Araştırma, İstanbul’da Sosyal Hizmetler Çocuk Esirgeme Kurumuna bağlı bir huzurevinde 5 Kasım - 29 Aralık 2007 tarihleri arasında yürütülmüştür. Evreni görüşmeye katılmayı kabul eden ve iletişim kurulabilen 95 yaşlı oluşturmuştur. Veriler, anket formu, Sayısal Ağrı Skalası ve Geriatrik Depresyon Ölçeği (GDÖ) ile yüz yüze görüşme yapılarak toplanmıştır. Bulgular: Huzurevinde yaşayan yaşlıların ağrı prevalansı %57.9 bulunmuştur. Ağrısı olanların ağrı şiddeti 3 ile 9 arasında değişmekte olup ortalama 6.18±1.75’tir. Ağrısı olanların %25.5’i ciddi (7-10 puan) ağrıya sahiptir. Hipertansiyonu, kol ve bacak güçsüzlükleri, uykusuzluğu olan ve akrabaları ziyarete gelen yaşlılar, istatistiksel olarak anlamlı düzeyde daha fazla ağrı hissetmektedirler (p<0.05). Yaşlılarda depresyon riski prevalansı %66.3’tür. Ağrının şiddeti ile depresyon ölçeği puan ortalaması arasında istatistiksel olarak anlamlı korelasyon yoktur (r=0.01; p=0.89). Bütün gün ve sızlayıcı türde ağrı çekenlerin GDÖ puan ortalamalarının diğerlerine göre istatistiksel olarak anlamlı derecede daha yüksek olduğu belirlenmiştir (p<0.01). Sonuç: Yaşlılarda ağrı olup olmama durumu ile GDÖ puan ortalamaları arasında istatistiksel olarak anlamlı fark bulunmamıştır (p>0.01). Anahtar sözcükler: Yaşlı, Depresyon, Ağrı, Ağrı Skala, Huzurevi.

Introduction: In this study was designed to investigate pain and depression status, relation between pain and depression, and influential factors in the elderly residing in a nursing home. Materials and Method: This investigation was performed in a nursing home that is linked to Social Services and Society for the Protection of Children between the dates October the 5th 2007 - December the 29th 2007 in Istanbul. The sample included 95 elderly who agreed to participate in interviews and who could be contacted to. Data were collected by a questionnaire, Numeric Pain Scale and Geriatric Depression Scale (GDS) during face-to-face interviews. Results: The prevalence of pain in old people that live in nursing home has determined as 57.9%. The prevalence of depression risk in old people is 66.3%. There is no statistically significant correlation between the severity of pain and the averages of depression risk scores (r=0.01; p=0.89). The average GDS scores of the elderly people who feel pain in whole day and who feel tingling pain have been determined higher than the others, and this is statistically significant (p<0.01). Conclusion: No statistically significant difference between presence of pain and average scores in GDS was determined (p>0.01). Keys words: Depression, Pain, Pain Scale, Nursing Home.
Bi̇r huzurevi̇nde kalan yaşlilarda aǧri ve depresyon ri̇ski̇
Keywords: Hemşirelik; Halk Sağlığı Hemşireliği; Sağlık Bilimleri; Nursing; Public Health Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing; Yaşlı; Depresyon; Ağrı; Ağrı Skala; Huzurevi; Depression; Pain; Pain Scale; Nursing Home